Rugby, race, and rhetoric : a thematic content analysis of constructions of race in the South African newspaper media in relation to South African rugby. - Kriel, Chris (My University, 2010)
This study aimed to explore the newspaper media’s constructions of blackness and whiteness as contained in a set of 84 articles published by the Independent Media Group in the same month (June) over four years (2005 to 2008). The data was collected using the Independent Media Online database. Various search strings were used and the final data set was drawn from an original sample of over 50 000 articles. The final set of 84 articles was examined using a thematic content analysis of the broad trends in relation to the constructions of blackness and whiteness in relation to black players specifically. This analysis revealed negative constructions of blackness such as black players being described as weak, lazy, and inherently lacking the skills, abilities and attributes to represent South Africa at a national level. The concurrent positive portrayal of whiteness results in white players being constructed as trustworthy, capable, meritorious and above all innately capable of playing rugby at an international level. Examples of black and white exceptionalism support the earlier findings regarding blackness and whiteness but take them further by examining examples that don’t fit the typical construction of race presented earlier.